Performance Investigation of Hydrostatic Transmission System as a Function of Pump Speed and Load Torque - Mandal S.K.; Singh A.K.; Verma Y.; Dasgupta K. (My University, 2025)
Every hydrostatic system requires a pump and a motor as its major components. Therefore, the operating parameters of the pump and the motor in a hydrostatic system are critical to the overall performance of the system. This paper evaluates the overall efficiency of the hydrostatic system based on the operating parameters of the pump and the motor, in this particular investigation they are the pump speed and the load torque, using the expressions obtained from the simple theory of Wilson (Hydraul Pneum Power 1:136–147, 1967). Many times in actual practice, various losses occurring in the hydrostatic system are not given proper consideration while the selection and design of the pump and the motor are made. The present article investigates the effects of the different loss coefficients of the pump and the motor on the overall performance of the system that may be useful for the selection of hydrostatic system and its components. © 2012, The Author(s).